Shear stress tracking control of an electrorheological fluid considering hysteresis non-linearity - Han, Y M; Choi, S B (Proceedings of the Institution of Mechanical Engineers. Part C, Journal of mechanical engineering science, 2004)
Abstract This paper presents shear stress tracking control of an electrorheological (ER) fluid actuator subjected to the hysteresis non-linearity. As a first step, polymethylaniline (PMA) particles are prepared and mixed with silicone oil to make an ER fluid. The Couette-type electroviscometer is employed to achieve the field-dependent shear stress. The Preisach model for the PMA-based ER fluid is identified using experimental first-order descending (FOD) curves. A compensation strategy is then formulated in a discrete manner through the Preisach model inversion to achieve the desired shear stress of the ER fluid. A proportional-intergal-derivative (PID) feedback controller is also integrated with the compensator in order to guarantee control robustness to uncertainty due to temperature-dependent hysteresis variation. The tracking performance of the control strategy is experimentally evaluated for two different desired shear stress trajectories.